Indicator mineral and till geochemical methods for kimberlite exploration in glaciated terrain (526cabe2-e08e-448c-950e-0f39e1fcecab) - M. B. McClenaghan (Canadian Institute of Mining, Metallurgy and Petroleum, 2002)
"This paper summarizes diamond exploration techniques used in glaciated terrain, focussing on indicator mineral and geochemical methods applied to glacial sediments. Understanding the ice flow history, depositional history, and stratigraphy of glacial sediments is essential to successful sampling, interpretation and follow-up of indicator mineral and geochemical anomalies related to kimberlites. Kimberlite indicator minerals survive glacial transport over long distances and the relative abundance of each mineral in till is a function of the primary mineralogy of individual kimberlites. Indicator mineral distributions observed at a regional scale define the net effect of glacial dispersal, often along different ice flow directions. Local-scale distributions define individual dispersal trains. The medium sand (0.25 mm to 0.5 mm) fraction of heavy mineral concentrates, * GSC Contribution No. 2002028 prepared from glacial sediment samples, is best suited for indicator mineral surveys. The application of till geochemistry to diamond exploration is increasing because it is significantly cheaper than indicator mineral analysis and it can be performed quickly. The <0.063 mm (silt+clay) and 0.5 mm to 2.0 mm (coarse sand) fractions provide the best geochemical contrast between background and kimberlite-rich till. Kimberlite pathfinder elements that provide good contrast include Ni, Cr, Ba, Co, Sr, Rb, Nb, Mg, Ta, Ca, Fe, K, Ti and LREE, the relative importance of which will depend on kimberlite composition and that of the surrounding bedrock.IntroductionIn Canada, glacial erosion is the principal means by which kimberlite and its associated minerals have been dispersed, from a few tens of metres to tens of kilometres down-ice. Post-glacial weathering has had little impact on kimberlite debris in the glacial sediments, thus boulder tracing, indicator mineral methods and trace element geochemistry of the fine fraction of till (“drift prospecting” methods) can be used to detect kimberlite dispersal within areas covered by glacial sediment. This paper provides a summary of drift prospecting methods for kimberlite exploration in glaciated terrain, and includes examples of reconnaissance- , regional- and local-scale kimberlite indicator mineral and till geochemical distribution patterns.Weathered kimberlite is more susceptible to glacial erosion than the surrounding bedrock, thus many kimberlites in glaciated terrain are found in low or swampy ground, under small lakes, or covered by thin (< 1 m) to thick (>50 m) glacial sediments. Glacial erosion has removed varying amounts of the pre-glacially weathered kimberlite and, in some cases, the hard competent kimberlite below. For example, glacial erosion of the Peddie, McLean and Seed kimberlites near Lake Timiskaming, Ontario, removed pre-glacially weathered kimberlite, leaving a polished striated subcropping surface (McClenaghan et al., 1999a). In contrast, glacial erosion of the B30 kimberlite, near Kirkland Lake, Ontario (Fig.1), was much less vigorous and left a >10 m cap of soft and highly weathered dark green clay-rich kimberlite (McClenaghan et al., 1996). The thickness of remaining pre-glacially weathered kimberlite will influence the geophysical signature of the kimberlite."